Comparative study of flow rate- and material-dependent human plasma protein adsorption on oxygenator membranes and heat exchanger materials - Katharina Große-Berkenbusch; Meltem Avci-Adali; Patrick Cahalan; Linda Cahalan; Ana Velic; Boris Maček; Christian Schlensak; Hans Peter Wendel; Sandra Stoppelkamp (Frontiers in Cardiovascular Medicine)
Artificial lungs support patients with acute or chronic lung diseases. However, complications such as the activation of blood components leading to thrombosis and inflammation limit their long-term applicability. The systematic characterization of protein adhesion events on different material parts of the oxygenators at different flow rates can shed light on the initial reaction of blood to foreign materials. Miniaturized extracorporeal circuit devices with heparin-coated gas (PMP) or heat-exchange (PET) hollow-fiber membranes were exposed to high and low flow rates. Hemocompatibility and adsorption of plasma proteins were measured after one minute to six hours using mass spectroscopy analyses. Approximately 150–200 different proteins were present on the membranes, with almost no variation in the 10 most abundant proteins. Protein adsorption to the membrane types did not vary to a large extent, but a decreased flow rate significantly reduced the differences in protein adsorption between both membrane types and led to the adhesion of significantly higher amounts of inhibitory proteins C1INH and α1-AT. At the higher flow rate, coagulation-associated proteins adsorbed significantly more to PET membranes, whereas complement-activating-related proteins adsorbed more on PMP membranes. Our results highlight the importance of analyzing all circuit components to understand the activation of blood components during ECMO. The primary contributor to increased protein adsorption and activation of blood components was an increased flow rate. Therefore, flow rate adjustments should ideally aim to achieve optimal oxygenation levels of around 80% while minimizing protein adsorption and blood activation during ECMO. Notably, at a low flow rate, PMP HFM exhibited a significant increase in binding of complement and inflammation inhibitors, suggesting a potential benefit of lowering the flow rate apart from the general reduction in protein adsorption.